Development, Implementation and Evaluation of a Professional Skills Development Program: The Case of Concordia University’s GradProSkills - Venkatesh, Vivek; Rabah, Jihan; Lamoureux-Scholes, Laurie; Pelczer, Ildiko; Urbaniak, Kathryn; Martin, Frédérica (Canadian Journal of Higher Education, 2014)
The Graduate and Professional Skills (GradProSkills) program is an initiative developed and run by Concordia University’s School of Graduate Studies and the university’s Office of the Vice-President, Research and Graduate Studies. This paper presents a case study in which we describe the development, implementation, and evaluative components of the GradProSkills program. Drawing on data from a rigorously validated workshop evaluation tool and from attendance figures spanning a period of a little over two and a half years, we provide a picture of how Concordia’s graduate students are benefiting from the GradProSkills program. We present the results of both descriptive and inferential statistical analyses run on a pilot group of registrants who provided evaluation data (n = 3,292). Our case study contributes an empirically derived model of extracurricular programming, with contextualizing details of administrative structures, curriculum-development initiatives, and partnership efforts that have been used in operating the GradProSkills program.